Managerial perception on the application of the balanced scorecard evaluation approach - Shrestha, Prakash (NCC Journal, 2020)
This study aims to examine the managerial perception of the application of the balanced scorecard (BSC) evaluation approach. It considers the main four perspectives of the BSC evaluation approach including the financial, the customer, the internal processes, and the learning and growth perspective. This study is primarily descriptive in nature. The questionnaire was delivered to nine commercial bank managers, including three state-owned banks, three joint-venture banks, and three private banks. A total of 180 questionnaires were distributed to them, and 129 (71.67%) were returned and used. The results reveal that Nepalese bank managers have a perception of a better financial position. They use the financial perspective as an important aspect of the BSC evaluation approach when measuring bank performance. In terms of customer perspective, the results show that banks have better customer connections. It also suggests that Nepalese bank managers believe that using customer viewpoints is critical to the performance of their institutions. In practice, both the internal process and the learning and growth perspective appear to be fair. As a result, Nepalese commercial banks succeed in each of the four aspects of the BSC evaluation approach.